Development of Deep Dialogue Learning Film to Improve Digital Literacy and Device Control in Students in Pre-Welfare Families - Stevanus Galih Febriawan; C Asri Budiningsih; Marwan Marwan; Agus Herwanto; Agung Prihatmojo (AL-ISHLAH: Jurnal Pendidikan, 2025)
Uncontrolled gadget use among students, particularly those from underprivileged families, presents a growing concern due to limited access to digital literacy education. This study aims to develop a Deep Dialogue-based learning film as an educational medium to enhance digital literacy and promote responsible device use among students and their parents. The study employed a Research and Development (RD) approach, following a series of stages: needs analysis, design, product development, testing, and evaluation. Participants included students from underprivileged families and their parents. Data were gathered through observations, interviews, and questionnaires and analyzed descriptively to assess the product's effectiveness. The results demonstrate that the Deep Dialogue learning film effectively increased awareness of digital literacy among both students and parents. It also supported parents in guiding and controlling their children’s use of digital devices more effectively. The film’s accessibility and relevance to the target audience contributed to its positive reception and usability. The Deep Dialogue approach successfully engaged both students and parents in meaningful discussions about digital responsibility, self-control, and the wise use of technology. Its integration into a film medium made the content more relatable and accessible, especially for families with limited educational resources. The developed learning film proved effective in improving digital literacy and device-use management in underprivileged families. Future research should focus on expanding the film's content to include broader aspects of digital literacy and character education.